Exploring Homestay Tourism in Nepal: Unveiling Opportunities and Challenges - Kafle, Dol Raj (Historical Journal, 2023)
Homestay tourism is a form of accommodation that allows tourists to stay with local families, immersing themselves in the country’s rich culture, traditions, and hospitality. This paper explores the historical roots of homestays, originating from ancient customs of hospitality in various civilizations. The objective is to investigate the role of homestays in promoting rural tourism, supporting local economies, and providing authentic travel experiences. Homestay tourism offers a family-like environment for tourists, serving as an alternative to building hotels in remote areas, which contributes to conserving local forests and reducing costs. The development of rural tourism has positively impacted the income and living standards of local communities, offering employment opportunities, and enhancing cultural preservation. However, challenges persist, such as insufficient infrastructure development, unclear policies, limited use of local products, and inadequate training for homestay operators. Addressing these challenges systematically is essential for the future success of homestay tourism in Nepal. By investing in infrastructure, formulating clear policies, promoting the use of local products, and providing training, homestay tourism can continue to thrive, offering travelers an authentic experience and benefiting local communities.